Debunking Myths about the American Presidential Elections of 2016 and Failures in the Social Sciences - Weaver, Eric Beckett (METSZETEK Társadalomtudományi Folyóirat, 2017)
Throughout the campaign and following the elections of 2016, the two major political partiescherished stories about what happened, and why it happened. Some of these stories have somebasis in fact, while others are completely mythical, and nevertheless believed. These stories, ormyths, arise from the political desires and belief systems of those who tell them. In what followswe will examine these stories in the lights of the facts